Water quality monitoring using wireless sensor network and smartphone-based applications: a review - Abdul Rahim, Herlina; Zulkifli, Syahidah Nurani; Mohd Subha, Nurul Adilla; Abdul Rahim, Ruzairi; Zainal Abidin, Hafilah (IFSA Publishing, 2017)
A wireless sensor network (WSN) has a huge potential in water ecology monitoring applications. The integration of WSN to a portable sensing device offers the feasibility of sensing distribution capability, on-site data measurements, and remote sensing abilities. Due to the advancement of WSN technology, unexpected contamination events in water environments can be observed continuously. Local Area Network (LAN), Wireless Local Area Network (WLAN) and Internet web-based are commonly used as a gateway unit for data communication via local base computer using standard Global System for Mobile Communication (GSM) or General Packet Radio Services (GPRS). However, WSN construction is costly and a growing static infrastructure increases the energy consumptions. Hence, a growing trend of smartphone-based application in the field of water monitoring is a surrogate approach to engage mobile base stations for in-field analysis that are driven by the expanding adaptation of Bluetooth, ZigBee and standard Wi-Fi routers. Owing to the fact that smartphones are portable and accessible, mobile data collection from WSN in remote locations are achievable. This paper comprehensively reviews the detection of water contaminants using smartphone-based applications in accordance with WSN technologies. In this paper, some recommendations and prospective views on the developments of water quality monitoring will be discussed.